QUICK RESPONSE CODES IN IMPROVING STUDENTS' VOCABULARY MASTERY : classroom action research in one vocational high school in Cimahi - Sriyuliyanti, _ (2017)
Penelitian ini bertujuan untuk mengetahui apakah penerapan Quick Response Codes bermanfaat bagi siswa dalam meningkatkan kosa kata bahasa Inggris mereka. Penelitian ini menggunakan desain Penelitian Tindakan Kelas (Classroom Action Research / CAR) dimana peneliti bekerja sama dengan seorang pengamat di kelas. CAR terdiri dari dua siklus dengan langkah-langkah perencanaan, akting, pengamatan dan refleksi dalam setiap siklus. Data dikumpulkan melalui beberapa prosedur, yaitu observasi, kuesioner, wawancara, dan tes. Hasil penelitian ini menunjukkan bahwa ada peningkatan pemenuhan kriteria penguasaan minimum dari 0% sebelum perlakuan menjadi 14,28% setelah siklus 1 dan 77,14% setelah siklus 2. Dengan demikian, kriteria keberhasilan tercapai. Sama pentingnya, hasil kuesioner menunjukkan bahwa siswa merespon positif terhadap penggunaan Quick Response Codes dalam pengajaran kosa kata. Demikian juga, hasil observasi menunjukkan bahwa siswa secara aktif berpartisipasi dalam proses pembelajaran dengan menggunakan Quick Response Codes dalam pembelajaran kosa kata dan mendukung keterlibatan mereka di kelas. Kedua hasil tersebut didukung oleh tanggapan positif dari siswa terhadap penggunaan Quick Response Codes, seperti yang diungkapkan melalui kuesioner, dan pendapat positif kolaborator mengenai penggunaan media pembelajaran, sebagaimana dibuktikan dalam wawancara.;--- This study was aimed to investigate whether the implementation of Quick Response Codes is useful for the students in improving their English vocabulary. This study employed a Classroom Action Research (CAR) design in which the researcher worked collaboratively with an observer in the class. The CAR consisted of two cycles with the steps of planning, acting, observing and reflecting in each cycle. The data were gathered through several procedures, i.e. observation, questionnaire, interview, and tests. The result of this study showed that there was an increase in the students' fulfillment of minimum mastery criterion from 0% before the treatment to 14.28 % after cycle 1 and 77.14 % after cycle 2. Accordingly, the criterion of success was achieved. Equally important, the result of the questionnaire showed that the students responded positively towards the use of Quick Response Codes in teaching vocabulary. Likewise, the results of observation revealed that the students actively participated in the learning process by using the Quick Response Codes in the vocabulary learning and it supported their engagement in the class. The two results were supported by the positive responses from the students to the use of Quick Response Codes, as revealed through the questionnaire, and the positive collaborator's opinion on the use of the instructional media, as evidenced in the interview.